Firing the Furnace? - An Econometric Analysis of Utilities' Fuel Choice - Harald Tauchmann (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2004)
This paper attempts to predict the potential effects of CO2 emissions trading on fuel choice in the German electric power industry. By analyzing panel data (1968-1998) of major utilities, we show that the fuel mix of electric utilities is price inelastic. As a consequence, the implementation of a CO2 trading scheme will, if anything, only slightly induce interfuel substitution. Accordingly, low-carbon fuels will hardly replace lignite and hard coal through CO2 emissions trading, as long as abatement targets are not extremely ambitious. However,one cannot rule out that fuel prices may become more important for the utilities' fuel mix as a result of deregulation in the German power sector.
Keywords: Q42; Q53; 330; fuel mix; high-carbon fuels; CO2 emissions trading; Elektrizitätswirtschaft; Brennstoff; Fossiler Energieträger; Emissionshandel; Schätzung; Deutschland